Engineering Auger recombination in colloidal quantum dots via dielectric screening - Xiaoqi Hou (Nature Portfolio, 2019)
Designing core/shell quantum dots with desired optoelectronic properties remains a challenge. Here, the authors investigate the negative and positive trions dynamics within a quantum dot, proposing an Auger engineering strategy based on geometry-dependent dielectrics for tuning optical properties.